The Artificial Neural Network Predicts The Number Of Smart Indonesian Card Recipients Using The Backpropagation Algorithm - Shella Nadya; Yani Maulita; Magdalena Simanjuntak (CV. AFDIFAL MAJU BERKAH, 2022)
The Smart Indonesia Card is a form of implementing the Smart Indonesia Program which is the flagship program of President Joko Widodo. The Smart Indonesia Card program supports the realization of the 9-year compulsory education program for basic education and universal secondary education or 12-year compulsory education. However, in essence, in processing the Smart Indonesia Card, errors still occur in predicting the needs of students who really need the assistance. Unpredictable gifts include students per department. In dealing with the provision of Indonesia Smart Card assistance, predictions are needed in the distribution of funds so that the distribution can be carried out evenly according to students who need the Indonesia Smart Card funds.